Good teaching and learning : Pupils and teacher speak - Morgan, Colin; Morris, Glyn. (Buckingham : Open University Press, 1999)
This book is about the particiants' views of learning and teaching in British comprehensive schools. It derives from the spoken views of pupils and teachers collected in ten schools over a period of five years in the mid-1990s, atime when government was dramatically changing the whole pattern of control of state provided education.
Keywords: High school teaching; Evaluation; Case studies; High school teaching -- Great Britain -- Evaluation -- Case studies; Learning -- Evaluation -- Case studies; Teachers -- Self-rating of -- Great Britain -- Case studies; Comprehensive high schools -- Wales -- Case studies